Preliminary design water ambulance untuk pemindahan pasien covid 19 di wilayah kepulauan Indonesia (studi kasus di kepulauan Madura) - Irmiyana, Triyanti; Siswanti, Heni; Musta'in, Muhammad (Politeknik Negeri Madura, 2022)
Based on data from the Sumenep Health Office, the number of positive confirmed cases of Covid on Talango Island was 9 people and 1 person died. One of the reasons is that there are no corona treatment facilities on the island, so they have to be referred to the Sumenep Regency hospital by boat. In this study, the design of a speed boat ambulance specifically for Covid-19 patients with a catamaran hull type. The purpose of the speed boat ambulance design is to handle island patients, especially Covid-19 cases during sea journeys to Sumenep Hospital with adequate facilities. The research method is carried out by determining the main size of the ship using the sister ships method, then proceeding with drawing lines plan, calculating ship resistance along with determining engine power, and general arrangement. The results obtained are in the form of the main size of the ship in the form of a Catamaran ship type; LOA : 13.0 m; B : 7.0 m; H : 2.0 m; T : 1.2 m; Vs : 16 knot. Has 3 accommodation rooms, including a patient room for 2 people; Medical staff room with 1 doctor, 2 medical staff and 2 patient's families; The wheelhouse with 2 crew members.